Prevalence of Anxiety Disorders in Iranian Men in the Last 10 Years: A Systematic Review and Meta-Analysis - Samadaee Gelehkolaee, Keshvar; Moamer, Soraya; Mohammadi Kalhori, Soroush; Aliakbari, Fereshteh; Shojaeefar, Ehsan; Pashapour, Sedigheh; Darab, Mehraneh; Hamdieh, Mostafa; Hosseini, Jalil (Archives of Men's Health, 2022)
Objective: To conduct a systematic review and meta-analysis to provide an estimate of the prevalence of anxiety disorders during 2010-2020 among Iranian men. Methods: We searched international and national databases including PubMed, Scopus, Cochrane library, SID, and Magiran with related keywords. The selected studies were also qualitatively evaluated using the Newcastle-Ottawa Scale (NOS) checklist. I2 test was used to measure the heterogeneity of the studies and a random strategy for meta-analysis was considered using the result. Results: We reviewed 782 articles identified through our search. Then, 51 articles were selected according to the inclusion criteria and, data were extracted from 24 articles. After carefully reviewing these articles, 24 articles were ultimately selected for meta-analysis. The overall estimated prevalence of anxiety among men was 12% (95% CI: 0.11, 0.13). The highest prevalence of anxiety was 50% (95%CI: 0.38-0.62) in Tehran and the lowest prevalence of anxiety was 0.014% (95%CI:0.003-0.025) in Shiraz. Conclusions: Anxiety disorders are common and the substantive identified here explain much of the prevalence of mental disorders. These results showed the potential in men to suffer from anxiety disorders.